A facile strategy to construct flexible and conductive silk fibroin aerogel for pressure sensors using bifunctional PEG. (15th June 2021) - Yuan, Jingjing; Yan, Biaobiao; Zhou, Man; Wang, Ping; Yu, Yuanyuan; Yuan, Jiugang; Wang, Qiang
Graphical abstract: Highlights: Bifunctional PEG endows SF aerogel with flexibility and structural stability. cPEG promotes pyrrole binding onto SF scaffold and PPy deposition. Flexible and conductive SF aerogel exhibits potential as a pressure sensor. Abstract: Silk fibroin (SF) has excellent biocompatibility and can be regenerated to obtain diverse materials. However, high brittleness and poor elasticity limit its applications in flexible devices, mainly due to high amounts of β -sheet structures in SF. Herein, a flexible SF aerogel is prepared by coupling polyethylene glycol (PEG) containing double-carboxyl end group with fibroin chains. This is followed by ammonium persulfate (APS)-initiated deposition of polypyrrole (PPy) units onto the scaffold. The bifunctional PEG not only improves the elasticity of SF aerogel, but it also promotes the accumulation of pyrrole cations on the fibroin surface and guides the formation of PPy. Meanwhile, PPy distributed in the SF matrix forms an electrically conductive pathway with an encouraging static conductivity, which is responsive to environmental humidity and external pressure. The sensitivity of the prepared SF-based conductive aerogel as a pressure sensor is much better than those reported in literature. Meanwhile, the stress and resistance show good synchronization during cyclic compressions. The present work provides a promising alternative for the fabrication of fibroin-based flexible and conductive aerogels as highly sensitive pressure sensors.